Perancangan Perangkat Lunak Penggambaran Grafik Berserta Penyelesaian Fungsi Persamaan Linear dan Kuadrat - Chandra, Tintin (Jurnal TIMES, 2017)
Human life always relate to the mathematics. Some life problem in modeled with the mathematics. Modeling represent the simplification from problem which realita, hence in a few solution modeling in finished with the graph. Graph yielded can be in the form of the straight line (linear), square, and also the other. Graph depiction stem from previous calculation have been processed or calculated. Linear function equation have the makings where highest rank of variable equal one, common form linear equation function is f(x) = ax + b. For the equation of square have the makings where highest rank variable of variable equal two. Form of equation square is f(x) = ax2 + bx + c. All constants of linear equation function and square represent the integer. Method in scheme of graph depiction use Visual Basic.Net is method waterfall. Groove the process use the flowchart to evaluate the scheme. Depiction scheme expected can assist the student, student in graph depiction especially linear graph and square. Result expected in the form of graph and calculation.